Pemberdayaan Potensi Lokal Untuk Pengembangan Desa Wisata Yeh Embang Kangin - I Gde Suranaya Pandit (Scopus ID: 57205029330) (Postgraduated Community Service Journal, 2020)
One of the villages in Jembrana Regency, Mendoyo Subdistrict, Yeh Embang Kangin Village which is a village has local potential for development into a tourist village, so that it can provide a change in impact for the people in the form of increased knowledge and economy of the local people. Therefore, the community empowerment program at Yeh Embang Kangin Tourism Village can develop into an agrotourism village, a spiritual tourism village and a marine tourism village and is equipped with culinary tourism. This type of research is a field research with descriptive analysis research specifications. Data sources are divided into primary data sources and secondary data sources. This research was conducted in Yeh Embang Kangin Village, Jembrana Regency. The research techniques used in this study are Milles, Saldana, and Huberman. From the results of the research conducted, it can be concluded that Yeh Embang Kangin Village in the north which is a mountainous area and dense forest, needs to be preserved as a source of water for the lives of its people. Yeh Embang Kangin Village as an agricultural area, can be managed to become a very attractive agro tourism attraction, starting from the nursery process, crop management, harvesting process, yield processing, and various kinds of processed products that are followed by quality standards. Spiritual Tourism Area about the existence of Rambut Siwi Temple which needs to be preserved. And marine tourism with surfing and snockling attractions to find out the biodiversity of marine life.